Exploring Differential Effects of Mathematics Courses on Mathematics Achievement - Ma, Xin; McIntyre, Laureen (Canadian Journal of Education/Revue canadienne de l’éducation, 2005)
Using data from the Longitudinal Study of Mathematics Participation (N = 1,518 students from 34 schools), we investigated the effects of pure and applied mathematics courses on mathematics achievement, controlling for prior mathematics achievement. Results of multilevel modelling showed that the effects of pure mathematics were significant after adjusting for traditionally important student‐level predictors of achievement and for school effects. The effects of mathematics courses varied significantly across schools. Students taking pure mathematics achieved higher in smaller schools, particularly schools with higher teacher commitment. Students taking applied mathematics achieved higher if they attended smaller schools. Keywords: mathematics achievement; mathematics courses; multilevel modeling, Alberta education À l’aide de données tirées de la Longitudinal Study of Mathematics Participation (N = 1518 élèves dans 34 écoles albertaines), les auteurs ont étudié les effets des cours de mathématiques pures et appliquées sur les compétences en mathématiques en tenant compte des compétences antérieures. Les résultats de la modélisation multiveau, une forme des modèles statistiques hierarchiques linéaires, indiquent que les effets des mathématiques pures sont significatifs une fois pris en compte les prédicteurs de réussite les plus fréquents ainsi que les effets des écoles. Les effets des cours de mathématiques variaient d’une école à l’autre. Les élèves en mathématiques pures ont obtenu de meilleurs résultats dans les écoles de plus petite taille, surtout dans celles où les enseignants s’impliquent davantage. Les élèves en mathématiques appliquées ont eux‐aussi obtenu de meilleurs résultats dans les écoles de plus petite taille. Mots clés: réussite en mathématiques, cours de mathématiques, modélisation multiniveau, éducation en Alberta.